BASICS OF REGULATION OF DISPARITIES IN THE DEVELOPMENT OF SOCIO-ECONOMIC SPHERES OF THE REGIONS - Mullabayev Baxtiyarjon Bulturbayevich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
Opinions and comments about the basis of regulation of disparities in the development of the socio-economic spheres of the regions are presented.